2021
DOI: 10.3390/ijms222111649
|View full text |Cite
|
Sign up to set email alerts
|

Murine Oncostatin M Has Opposing Effects on the Proliferation of OP9 Bone Marrow Stromal Cells and NIH/3T3 Fibroblasts Signaling through the OSMR

Abstract: The IL-6 family cytokine Oncostatin M (OSM) is involved in cell development, growth, hematopoiesis, inflammation, and cancer. Intriguingly, OSM has proliferative and antiproliferative effects depending on the target cell. The molecular mechanisms underlying these opposing effects are not fully understood. Previously, we found OSM upregulation in different myeloproliferative syndromes. However, OSM receptor (OSMR) expression was detected on stromal cells but not the malignant cells themselves. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…6b , Supplementary Fig. 10 ), because these cells express gp130, LIFR and IL-11R 45 . Dose-dependent cellular stimulation showed 10–100 ng/ml of GIL-11 and IL-11 were needed to achieve sustained STAT3 phosphorylation in murine NIH/3T3.…”
Section: Resultsmentioning
confidence: 99%
“…6b , Supplementary Fig. 10 ), because these cells express gp130, LIFR and IL-11R 45 . Dose-dependent cellular stimulation showed 10–100 ng/ml of GIL-11 and IL-11 were needed to achieve sustained STAT3 phosphorylation in murine NIH/3T3.…”
Section: Resultsmentioning
confidence: 99%
“…Jakob et al, reported that there is evidence for mOSM signaling involving both OSMR and LIFR in bone formation and resorption [ 8 ]. They showed that mOSM had a proliferative effect on a fibroblast cell line and an antiproliferative effect in bone marrow stromal cells.…”
mentioning
confidence: 99%